A prospective, randomized, double-masked trial on radiation therapy for neovascular age-related macular degeneration (RAD study) - Völcker, Hans Eberhard; Holz, Frank G.; Unnebrink, Kristina; Bellmann, Caren; Debus, Jürgen; Pritsch, Maria; Wannenmacher, Michael (Ophthalmology, 1999)
Objective - To determine the efficacy of external beam radiation therapy on choroidal neovascularization (CNV) secondary to age-related macular degeneration (ARMD). - Design - Multicenter, parallel, randomized, double-masked clinical trial performed at nine ophthalmic and radiotherapeutic centers. - Participants - Two hundred five patients were randomly assigned either to treatment with 8 fractions of 2 Gy external beam irradiation (n = 101) or to control with 8 fractions of 0 Gy (sham treatment, n = 104). Both patients and ophthalmologists were masked with regard to applied treatment. Patients with subfoveal classic or occult CNV, visual acuity of 20/320 or greater on the Early Treatment Diabetic Retinopathy Study chart, lesion size of 6 disc areas or less, history of visual symptoms of 6 months or less, and absence of foveal hemorrhage were recruited. - Intervention - In the treatment group, external beam irradiation with 8 fractions of 2 Gy was performed, whereas in the control group, sham treatment with 8 fractions of 0 Gy was applied. - Main outcome measures - Primary outcome measure was the difference in visual acuity between baseline and after 1 year of follow-up. - Results - One hundred eighty-three patients (89.3%) completed the 1-year follow-up. The mean reduction in visual acuity was 3.5 ± 4.7 lines in 88 patients of the 8- × 2-Gy treatment group and 3.7 ± 3.8 lines in 95 patients of the 8- × 0-Gy control group. This difference was not statistically significant (P = 0.53, Mann-Whitney U test). At 1 year, 51.1% of treated patients and 52.6% of control subjects lost three or more lines (P = 0.88). Visual acuity in the presence of classic CNV dropped by 3.7 ± 4.4 lines in 33 patients of the treatment group versus 4.3 ± 3.9 lines in 36 patients of the control group (P = 0.47). Visual acuity in 114 patients with occult CNV dropped by 3.4 ± 4.9 in the treatment group (55 patients) versus 3.4 ± 3.8 lines in the control group (59 patients) (P = 0.80). - Conclusions - In this randomized study, radiation therapy at a dose of 16 Gy applied in 8 fractions of 2 Gy provided no benefit as a treatment for subfoveal CNV secondary to ARMD at 1 year.
Available online: 25 August 2003
Gesehen am 03.03.2021